DEVELOPMENT OF SYSTEMS OF MULTIPLEX PCR TO IDENTIFY GENES OF RESISTANCE TO MAGNAPORTHE GRISEA (HERBERT) BARR. AND SELECTION OF NEW RESISTANT FORMS (DONORS) ORYZA SATIVA L. TO PATHOGEN - E. V. Dubina; P. I. Kostylev; L. V. Esaulova (Зерновое хозяйство России, 2018)
Imperfect fungus Magnaporthe grisea is a phyto pathogen with a vast influence on most crops including rice. Economic damage of the disease is enormous in all rice cultivation zones of the world. The purpose of the work is to create some cultivars and lines of rice with tree and more genes resistant to pyriculariosis using the method of molecular marking. We introduced and pyramided of Pi-ta, Pi-b, Pi-1, Pi-2, Pi-33 genes resistant to pyriculariosis into domestic cultivars of rice to give them longer resistance to the disease. DNA-markers analysis allowed revealing disease resistant rice samples which possess 5 aimed genes in homozygous condition. The results of phyto pathological testing showed their resistance to a mixture of isolators of M.grisea pathogen, found in Krasnodar Krai.  To increase economic efficiency of marker-assisted selection we developed a system of multiplex PCR which can simultaneously identify three Pi-1+Pi-2+Pi-33 genes resistant to M. grisea in a DNA genome of hybrids under one PCR. Its use allows reducing costs of material and time for analyzing of rice samples.